Utilization of a Web-Based Diagram Application as an Alternative to Visio in Computer Application Practicum - Syafran Nurrahman (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study is motivated by the need for students to develop competencies in creating process diagrams and system models in the Computer Applications course as part of their professional skills in the field of information technology, as well as the challenges associated with the use of licensed, paid diagram software in practical learning activities. The purpose of this study is to analyze the utilization of a web-based diagram application (Draw.io) as an alternative to Microsoft Visio in supporting the implementation of computer application practicums in higher education. The research subjects consisted of eight selected students enrolled in a single Computer Applications class at a higher education institution. This study employed a quasi-experimental approach, with data collection techniques including observation of practicum outcomes, distribution of questionnaires to students, and semi-structured interviews with selected students to obtain supporting data related to their experiences in using the web-based diagram application. The results indicate that the utilization of the web-based diagram application (Draw.io) improved students’ ability to create process diagrams and system models, as evidenced by an increase in the average score from 69.2% in the pretest to 82.6% in the posttest, representing an improvement of 13.4 percentage points. In addition, students’ perceptions revealed that the web-based diagram application is easy to use, flexible in terms of access, and feasible to be used as a supporting medium for practicum activities. This study is expected to provide a practical alternative solution for educational institutions in supporting computer application practicums and to contribute to the development of efficient and sustainable technology-based learning.